The Brazilian real estate securitization market: determinants of pricing - Cazassa, Eduardo Fernandes (2016)
The pricing of Real Estate Receivables Certificates (CRIs) is investigated in relation to the underlying assets and level of guarantees, as far as volume, maturity and rating variables are controlled for. An added average premium of 1.0 p.p. is seen in CRIs, compared with the same maturity and rating debentures. This premium is motivated by two facts: (a) although CRIs follow relative standardization, we find that they can represent different levels of risk and underlying assets; and (b) this lack of standardization leads to different pricing levels for their specific risk characteristics. The different risk levels are perceived by the different guarantees used – for instance, 41% of issuances include personal guarantees of the originators. We conclude that there is a positive difference of returns (the average spread for the inflation-indexed CRIs at issue was 321 bps higher than the market yield curve) being more prominent depending on the segment (premium for the residential and allotment segments) mitigated by the level of guarantees offered. It is possible to verify an average premium of 1.4 p.p. in both residential and allotments. Important issuance characteristics were analyzed as control (volume, maturity, rating grades and origin of the rating agency). Larger and longer-maturity CRIs show a significant lower spread. Residential CRIs show a positive effect (lower spread) when assessed by any rating agency whereas commercial CRIs show a negative effect (higher spreads) simply due to the fact of being rated. The commercial CRIs can also show a positive effect (lower spread) for issuances rated above ‘A’ or if they are assessed by an international rating agency.